Recent progress and future perspectives of flexible metal‐air batteries. (22nd December 2021) - Li, Tingzhen; Peng, Xinwen; Cui, Peng; Shi, Ge; Yang, Wu; Chen, Zehong; Huang, Yongfa; Chen, Yongkang; Peng, Jinyuan; Zou, Ren; Zeng, Xiaoyan; Yu, Jian; et al.
Abstract: With the rapid development of wearable and intelligent flexible electronic devices (FEDs), the demand for flexible energy storage/conversion devices (ESCDs) has also increased. Rechargeable flexible metal‐air batteries (MABs) are expected to be one of the most ideal ESCDs due to their high theoretical energy density, cost advantage, and strong deformation adaptability. With the improvement of the device design, material assemblies, and manufacturing technology, the research on the electrochemical performance of flexible MABs has made significant progress. However, achieving the high mechanical flexibility, high safety, and wearable comfortability required by FEDs while maintaining the high performance of flexible MABs are still a daunting challenge. In this review, flexible Zn‐air and Li‐air batteries are mainly exemplified to describe the most recent progress and challenges of flexible MABs. We start with an overview of the structure and configuration of the flexible MABs and discuss their impact on battery performance and function. Then it focuses on the research progress of flexible metal anodes, gel polymer electrolytes, and air cathodes. Finally, the main challenges and future research perspectives involving flexible MABs for FEDs are proposed. Abstract : Rechargeable flexible metal‐air batteries (MABs) have been regarded as promising energy storage/conversion devices for wearable and flexible electronic devices. Herein, an overview is reported to discuss the recent progress and current major dilemmas of flexible MABs, with the focus of Zn‐air and Li‐air batteries. Particularly, the design and preparation of flexible cathodes, metal anodes, and gel polymer electrolytes are highlighted, and their influence on electrochemical performance and functionality of the flexible MABs are further discussed. Additionally, the main technical hurdles and future research perspectives of flexible MABs for wearable electronic devices are proposed.